Goethite dissolution by acidophilic bacteria - Stanković, Srdjan; Schippers, Axel (Frontiers in Microbiology, 2024)
Previous studies have reported the role of some species of acidophilic bacteria in accelerating the dissolution of goethite under aerobic and anaerobic conditions. This has relevance for environments impacted by acid mine drainage and for the potential bioleaching of limonitic laterite ores. In this study, natural well-characterized goethite mineral samples and synthetic goethite were used in aerobic and anaerobic laboratory batch culture incubation experiments with ferric iron-reducing, acidophilic bacteria, including the lithoautotrophic species Acidithiobacillus (At.) thiooxidans, At. ferrooxidans, and At. caldus, as well as two strains of the organoheterotrophic species Acidiphilium cryptum. All bacteria remained alive throughout the experiments and efficiently reduced soluble ferric iron in solution in positive control assays. However, goethite dissolution was low to negligible in all experimental assays with natural goethite, while some dissolution occurred with synthetic goethite in agreement with previous publications. The results indicate that ferric iron-reducing microbial activity at low pH is less relevant for goethite dissolution than the oxidation of elemental sulfur to sulfuric acid. Microbial ferric iron reduction enhances but does not initiate goethite dissolution in very acidic liquors.